Prinsip Eco Art dalam Karya Recycle Limbah Tekstil “Night Queen” - Syahla, Khansa (Institut Seni Indonesia Yogyakarta, 2025)
The accumulation of textile waste due to excessive consumption patterns and fashion trends has become a significant environmental issue. The three-dimensional artwork titled Night Queen seeks to innovate through a recycling approach by transforming textile waste into textile clay. This new material is pliable and suitable for creating art pieces. The Eco-Art approach is applied to convey ecological messages while educating the public about the impact of textile waste. This study employs an artistic-based research method, incorporating shredded textile waste mixed with additional materials such as cornstarch, white glue, vinegar, liquid soap, and oil. The visualization of this artwork is inspired by the tuberose flower and eye elements, symbolizing the inferiority and sadness experienced by women. It utilizes mimesis aesthetic theory and a tetradic color scheme. The resulting artwork aims to motivate women to build self-confidence while contributing to environmental conservation and innovative textile waste management. ABSTRAKPenumpukan limbah tekstil akibat pola konsumsi berlebihan dan tren fashion telah menjadi permasalahan lingkungan yang signifikan. Karya seni tiga dimensi berjudul “Night Queen” inovasi melalui pendekatan recycle, dengan mengolah limbah tekstil menjadi textile clay. Sebuah material baru yang mudah dibentuk dan digunakan untuk pembuatan karya seni. Pendekatan Eco-Art diterapkan untuk menyampaikan pesan ekologis sekaligus memberikan edukasi kepada masyarakat tentang dampak limbah tekstil. Penelitian ini menggunakan metode artistic based research, mencampur limbah tekstil yang telah dicacah dengan bahan tambahan seperti tepung maizena, lem putih, cuka, sabun cair, dan minyak. Visualisasi karya ini terinspirasi oleh bunga sedap malam dan elemen mata sebagai simbol inferioritas dan kesedihan yang dialami wanita, dengan penerapan teori estetika mimesis dan kombinasi warna tetradic. Hasil karya berfungsi sebagai motivasi untuk meningkatkan kepercayaan diri wanita, sekaligus sebagai kontribusi dalam upaya pelestarian lingkungan dan inovasi pengelolaan limbah tekstil.